The fortitude factor for a quality of work-life among healthcare employees / Mohd Azrul Azman ... [et al.] - Azman, Mohd Azrul; Fuad, Nurwahida; Shahruddin, Shafiq; Aiman, Muhammad (Universiti Teknologi MARA Cawangan Sarawak, 2024)
This study aimed to investigate the relationships between work environment, leadership styles and job satisfaction as independent variables towards the quality of work-life as a dependent variable among healthcare employees. The study was conducted at the Health Office of Kangar Perlis, Malaysia, and employed a quantitative method using a questionnaire survey from 265 respondents out of a population of 811. The samples were analysed using SPSS for correlation and regression. The findings revealed significant relationships between all variables, including the dependent variable and the independent variables. Based on the obtained scores, this study concludes that the results have high reliability and validity, and all hypotheses were acceptable. The study's implications and recommendations are discussed in the conclusion section. Overall, this study contributes to the body of knowledge by providing empirical evidence of the relationships between work environment, leadership styles, job satisfaction, and quality of work-life among healthcare employees.